2020
DOI: 10.1080/00313831.2020.1754903
|View full text |Cite
|
Sign up to set email alerts
|

Multilingual Classrooms—Danish Teachers’ Practices, Beliefs and Attitudes

Abstract: Multilingualism is a major feature of European schools. Using the Multilingual Classroom questionnaire devised by the European Literacy Network, the current study examines Danish data from a questionnaire concerning teachers' behaviours, beliefs, and attitudes with regard to multilingualism in a Danish school setting. Sixty-one participants contributed to the Danish sample (85% females). The teachers who completed the questionnaire had a positive attitude to multilingualism, the value of maintaining and suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…A fifth general factor that captured the shared covariances of the four low-order factors, thus, representing teachers' attitudes directly, was further identified. Some data from single countries have now been published in country-specific journals using the MCQ (Knudsen et al 2020;Authors Mifsud & Vella, 2018a, b). The current study advances our understanding of attitudes to multilingualism by examining the effects of country of origin, gender and education level in which the teachers taught (elementary vs. secondary) on the four factors emerging from the MCQ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A fifth general factor that captured the shared covariances of the four low-order factors, thus, representing teachers' attitudes directly, was further identified. Some data from single countries have now been published in country-specific journals using the MCQ (Knudsen et al 2020;Authors Mifsud & Vella, 2018a, b). The current study advances our understanding of attitudes to multilingualism by examining the effects of country of origin, gender and education level in which the teachers taught (elementary vs. secondary) on the four factors emerging from the MCQ.…”
Section: Discussionmentioning
confidence: 99%
“…In areas of Wales, both English and Welsh are the languages of instruction (Gathercole and Thomas 2009), and in Catalonia, both Spanish and Catalan are used in some schools (Kirsch 2018a(Kirsch , 2018b. By contrast, in Denmark, three different official languages are used in schools (Knudsen et al 2020).…”
Section: The Pupilsmentioning
confidence: 99%
“…English language teachers' beliefs about teaching and learning have been the subject of plenty of research (Crusan et al, 2016;Hayes, 2009;Lee & Bathmaker, 2007;Liviero, 2017;Karabenick & Noda, 2004;Knudsen et al, 2021;Murphy & Torff, 2019;Nguyen et al, 2016). The study by Oder and Eisenschmidt (2018) exploring EFLTs' conceptions of effective teaching yielded that they strongly agreed with the statement that -teachers should vary their teaching methods to achieve students' meaningful learning and understanding‖, furthermore, they strongly favoured the statement that -students need to be given opportunities to discuss new ideas and listen to their classmates' ideas in small groups‖.…”
Section: Eflts' Beliefs Concerning Effective Language Teachingmentioning
confidence: 99%
“…Teachers with more experience in multilingual settings may display more positive attitudes toward multilingualism [44, 48]. Fluency in other languages [8, 38, 49] and socio-economic background of the teachers [50] modified their attitudes toward multilingual learners as well. Recent research of Alisaari et al [44], Portolés and Martí [51], and Pohlmann-Rother et al [52] showed that training teachers on concepts of multilingualism and language awareness had a positive effect on the attitudes of teachers.…”
Section: Introductionmentioning
confidence: 99%